Limitations on Ownership Rights: From Traditional Approach to Modern Trends - Nam, Do Giang (VNU Journal of Science: Legal Studies; Vol 39 No 3DO - 10.25073/2588-1167/vnuls.4515, 2023)
Theories of limitations on ownership rights are one of the foremost issues of property law. However, there is a lack of systematic and comprehensive studies on theoretical issues regarding the limitations of ownership rights in Vietnam, especially the issue of the social function of property law. This article aims to fill in this gap by systematically identifying and analyzing several prominent theoretical issues in limitations on ownership rights. Specifically, the article focuses on discussing: i) the new ideas of the qualitative duty/ qualitative obligation; ii) the principle of prohibiting the abuse of rights and the law of nuisance; iii) the need for external limitations on the right to exclude to balance the need for protection of other human rights; iv) the need to reform the traditional rule of limitations on ownership rights to meet the millennium goals of sustainable development.